Engineering maintainability how to design for reliability and easy maintenance - Dhillon, B. S. (Balbir S.), 1947-
In this work, Dhillo compiles information on designing modern engineering systems to reduce the time and expense required for maintenance, estimated by some to be typically over 60 per cent. He considers both traditional and innovative maintainability concepts and includes references